Recovery of Gold from Carbonaceous Ores at Carlin, Nevada - W. J. Guay; D. G. Peterson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
The extraction of gold from refractory ores containing activated carbon and various types of carbon compounds is being done commercially for the first time at Carlin, Nev., by Carlin Gold Mining Co. Oxidation of the carbonaceous materials to CO and CO,- is accomplished by the introduction of chlorine into an aqueous pulp. The chlorine reacts with the limestone in the ore to form calcium hypochlorite which in turn reacts with the carbonaceous matter to form calcium chloride, CO, and CO.. Following the oxidation treatment the ore is cyanided in the conventional manner. For the first six months of operation the plant averaged 83% extraction at a feed rate of 500 tpd and a consumption of 28.4 lb chlorine per ton of ore which showed only 33.5% extraction by conventional cyanidation without the oxidation pretreatment.